Bismuth Microparticles as Advanced Anodes for Potassium‐Ion Battery. Issue 19 (30th March 2018) - Huang, Jiaqiang; Lin, Xiuyi; Tan, Hong; Zhang, Biao
Abstract: Potassium‐ion batteries (KIBs) are important alternatives to lithium‐ and sodium‐ion batteries. Herein, microsized a Bi electrode delivers exceptional potassium storage capacity, stability, and rate capability by the formation of an elastic and adhesive oligomer‐containing solid electrolyte interface with the assistance of diglyme electrolytes. The kinetics‐controlled K–Bi phase transitions are unraveled combining electrochemical profiles, in situ X‐ray diffraction and density functional theory calculations. Reversible, stepwise Bi–KBi2 –K3 Bi2 –K3 Bi transitions govern the electrochemical processes after the initial continuous surface potassiation. The Bi electrode outperforms the other anode counterparts considering both capacity and potential. This work provides critical insights into the rational design of high‐performance anode materials for KIBs. Abstract : Bismuth microparticles with a high tap density are identified as a superior potassium‐ion storage material. The huge volume expansion of ≈406% is successfully buffered by the diglyme‐assisted formation of an elastic solid electrolyte interface, rendering stable electrochemical behavior. This work provides another critical strategy for large‐radius potassium storage by engineering the electrode–electrolyte interphase in addition to morphology optimizations.